Determinación de los contaminantes producto de la combustión por fuentes móviles a gasolina en el cantón La Maná, provincia de Cotopaxi, período 2017-2018. - Román Caisa, Jhony Javier (2018)
The investigation was carried out to determine the percentage of carbon monoxide (CO) and the parts per million of the unburned hydrocarbons (HC), generated by the internal combustion of vehicles with gasoline engines, in La Mana Cantón. Starting a diagnosis vehicle with information acquired from Agencia Nacional de Transito (ANT), in order to obtain a total number of vehicles registered in Cotopaxi Province. It was a reference to determine the sample resulting in 196 gasoline vehicles evaluated by Empresa Pública de Movilidad Tránsito y Transporte de la Mancomunidad de Cotopaxi, from La Maná, using the AVL DITEST Gas 1000 equipment, made measurements of free acceleration static test as stipulated by the Norma Tècnica Ecuatorina INEN 2203. Consecutively an analysis was carried out of the data with the Ecuadorian Technical Standard INEN 2204 determining compliance with the Compliance with CO and HC evidenced in the Rstudio software where the CO parameter 82.65% comply and 17.35% do not comply; while for the HC parameter, 72.44% comply and 27.56% do not comply. In Base to the sample point, in the vehicle registration center La Manà a simulation to the dispersion of the pollutants was carried out with software Rstudio, openair and the graph (polar plot) with data of the percentage of CO, the parts per million of HC and meteorological factors such as: wind speed, wind direction and temperature, downloaded as CSV format from Meteoblue meteorological platform; so evidencing the concentration and dispersion of the parameters under studies in several geographical directions.